Parasitic Infections - Khubchandani, Indru T.; Bub, David S. (Clinics in Colon and Rectal Surgery, 2019)
Parasitic infections of the gastrointestinal tract are a cause of morbidity to millions of individuals worldwide. These parasites are endemic in underdeveloped countries with poor sanitation allowing for spread through contaminated water supplies. While much is known about these parasites, the cutaneous manifestations caused by infection are infrequently reported in the literature. The deposition of the parasites into the perianal region often leads to significant skin irritation. Cutaneous findings vary from a mild pruritus ani to a macular rash to even severe perianal ulceration. This article discusses the perianal cutaneous findings caused by the parasitic illnesses, amebiasis, schistosomiasis, Enterobius vermicularis, strongyloidiasis, and cutaneous larva migrans, as well as their respective management.
Keywords: schistosomiasis; pinworm; cutaneous; parasite; colitis; dysentery; helminth; nematode; trophozoite; cercaria; filariform